CABG surgery in a patient with left iliac arteryocclusion: Precautions to consider - De la Peña Brush, Oscar F. (2015)
We present the case of an 82 years old male with Congestive Heart Failure (Left Ventricle Ejection Fraction: 20%) and Acute Pulmonary Edema secondary to Acute Myocardial Infarction that required Coronary Artery Bypass Graft (CABG) surgery. Past Medical History included Aortoiliac Occlusive Disease with total occlusion of the Left Iliac Artery and collateral circulation to the left inferior limb through the Left Internal Mammary Artery (LIMA).  CABG was perfomed without harvesting the LIMA due to high risk of legischemia. An attempt to revascularize the left limb previous to the cardiac surgeryin other to do so. Would have been too risky in this case. After 2 months follow up, patient showed good clinical outcomes.